A influência da certificação dos administradores de carteira brasileiros no desempenho de fundos de investimento - Rodrigo Lage d'azevedo Carneiro (2014)
The portfolio manager performs the management of financial resources from investors by executing purchase or sale of securities. For this activity in the country, it is necessary to obtain authorization from the CVM. The CVM emphasizes that the authorization does not imply any judgment on the merits of the administrator, nor any liability with respect to any unsatisfactory performance. It is clear the investor responsibility in properly select the portfolio manager to carry out the management of its resources. In this sense, it is fundamental to have a better know on how certain characteristics of mutual funds and portfolio managers influence the generation of performance. Specifically, we sought to determine whether there is influence of the professional certification of portfolio managers, along with other characteristics of the funds in the generation of performance. We considered the four certifications offered by ANBIMA: CGA, CPA - 10, CPA - 20 and CEA. The funds selected for inclusion in the study were equity funds active IBOVESPA, free equity and fixed income. The analyzed period was from January 2009 to July 2013. The analysis was performed using multiple linear regression technique with data arranged as cross section. The dependent variable of the econometric model was measured by two performance indexes, the Jensen's Alpha and Sharpe ratio. The explanatory variables were defined based on the literature: administration fee; performance fee; equity of the fund; type of fund management; and professional certification portfolio manager; and dummy variables for each of the management. The main contribution of this study was the finding that the certification management held by portfolio managers may be relevant for improving the performance aspect of Brazilian funds. The results, however, can not be assessed conclusively because there were not statistically significant. Another important contribution was the characteristic type of management. It was found that the independent management type, performed by external portfolio manager, might not be an important feature to improve performance. For the other evaluated characteristics, the results relating to the administration fee was in line with the provisions in the literature. Moreover, the results of the characteristics and performance fee and fund size showed itself at odds with the assumptions made.